The Old Man and Mr. Smith : a fable - Ustinov, Peter (New York : Arcade Publishing, 1990)
In his new novel, Peter Ustinov has chosen as his protagonists two of the most unusual characters of recent fiction. The Old Man is somewhat overweight and out of shape, wearing slightly tattered robes and sporting a pair of tennis shoes. Mr. Smith is small and dark, with a foul temper only occasionally relieved by a fiendish humor, and a disturbing aroma of sulfur that follows in his wake.
Keywords: ALLEGORIES